Researches hydraulic characteristics of a rotor-pulsation apparatus in processing of water-grain mix - Ободович, Александр Николаевич; Лымарь, Анна Юрьевна (Eastern-European Journal of Enterprise Technologies, 2014)
The most important feed-processing operation is the feeder grain refinement, which increases the surface area of grain material, improves the interaction between food and digestive enzymes. The equipment for carrying out this operation is still faulty because it does not allow obtaining a particle size of less than 500 microns. One of the most promising ways for improving production efficiency lies in using a rotor-pulsed apparatus based on the principle of a discrete-pulse energy input. The results of studying hydraulic properties of the rotor-pulsed apparatus when treating a water-grain mixture are given in the paper. Optimal treatment modes of the media were chosen. The performance of the RPA in dispersing grain mixture has been studied. It has been proved that these indexes together and separately affect the head and flow characteristics of the rotor-pulsed apparatus. The obtained results allow applying when desiging industrial facilities for slop feed preparation.